ENHANCING EFL LEARNERS’ WRITING SKILLS THROUGH BLOGGING - Lilis Suadah (Universitas Islam Negeri Banda Aceh, 2014)
This paper presents some reasons why English teachers aiming to increase their learners’ writing skills should use blogs in their teaching, particularly in EFL context. It is found that despite its drawbacks, putting pressure on computer illiterate learners and exposing them to non-standard English, blogging is an exceptional technological platform that offered learners numerous advantages such as it encourages them to write constructively, use English more frequently, and retain their motivation. This paper also highlights that to get most benefits of blogging, the teachers play major roles in ensuring the availability of reliable facilities (computer and the internet), teaching learners how to use blog purposefully, and controlling the bloggers (learners) to not only write their blog posts but also read, and provide feedback to their peers’.